HUKUM DAN URGENSI WAKAF TUNAI DALAM TINJAUAN FIKIH - Asri, Asri; Khaerul Aqbar; Azwar Iskandar (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This study aimed at determining the law and urgency of cash waqf in fiqh point of view in accordance with some views of fiqh scholars related to cash waqf. This research used a qualitative-descriptive approach with content analysis techniques and library research. The results showed that the scholars hold different views in deciding the law of cash waqf. Some scholars hold that the cash waqf is permissible. Some others hold that it is makruh (undesirable). There are even some scholars who forbid it. The author inclines toward the view that asserts its permissibility. The urgency and target of cash waqf is improvement of the economy and benefit in the world and the hereafter.